Research of congestions in urban transport network using cellular automation model - Jablonskytė, Janina; Ilgakojytė-Bazarienė, Jurga; Keršys, Artūras; Pakalnis, Algis (Transport, 2011)
The growing demand for transport and communication services leads to more and more important, traffic related and closely associated problems, especially in the city centre, such as traffic congestion, air pollution, noise and some others. When modelling traffic flows in the Kaunas city centre, the simulation models of crossroads were created based on the principle of cellular automaton model, taking into consideration such relevant traffic indicators as the average speed of traffic flow in different streets, traffic intensity, congestions and distributed flows. Operation of cellular automaton model is associated with the improved approach of further vehicle model. Modelling of microscopic traffic flows is based on the brake light–cellular automaton (BL–CA) model. Random functions were made discreet and autocorrelation values of these functions were calculated in this work. Fundamental macroscopic traffic characteristics were obtained. Numerical dependences of the average traffic speed and traffic flow, traffic density and traffic flow, the average traffic speed and density were determined, with a help of which the demand parameters of transport network were evaluated in the Kaunas city centre in certain time intervals.First Published Online: 07 Jul 2011